PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEUNGGULAN DAYA SAING BERKELANJUTAN BERDASARKAN REPUTASI UKURAN AKUNTANSI BUMN Tbk INDONESIA - Lubis, Tona Aurora; Putra, Wirmie Eka (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
This study aims to find and analyze models of the effect of ownership structure on the sustainable competitive advantage based on the reputation of the size of the accounting Indonesia’s privatized SOEs. The sample of this study a total of 14 SOEs Tbk Indonesia. Analysis of the data in this study using the Partial Least Square (PLS). Results penelitain found that increasing public ownership in the ownership structure of Indonesia’s privatized SOEs to improve sustainable competitive advantage based on the reputation of the accounting measure of increased return on equity (ROE), an increase in return on assets (ROA), an increase in the actual dividend payout ratio (ADPR).